Serious Mental Illness in the Nursing Home Literature: A Scoping Review. (6th May 2022) - Bucy, Taylor; Moeller, Kelly; Bowblis, John R; Shippee, Nathan; Fashaw-Walters, Shekinah; Winkelman, Tyler; Shippee, Tetyana
Nursing homes (NH) and other institutional-based long-term care settings are not considered an appropriate place for the care of those with serious mental illness, absent other medical conditions or functional impairment that warrants skilled care. Despite policy and regulatory efforts intended to curb the unnecessary placement of people with serious mental illness (SMI) in these settings, the number of adults with SMI who receive care in NHs has continued to rise. Through a scoping review, we sought to summarize the available literature describing NH care for adults with SMI from 2000 to 2020. We found that SMI was operationalized and measured using a variety of methods and diagnoses. Most articles focused on a national sample, with the main unit of analysis being at the NH resident-level and based on analysis of secondary data sets. Understanding current evidence about the use of NHs by older adults with SMI is important to policy and practice, especially as we continue to grapple as a nation with how to provide quality care for older adults with SMI.